Perancangan Sistem Informasi Akuntansi Penjualan Yoghurt Pada Koperasi Peternakan Sapi Bandung Utara dengan Menggunakan Microsoft Visual Basic 2005 dan MySQL Berbasis Client Server - Ai Suryati; Dony Waluya Firdaus (Labkat Press KA FTIK UNIKOM, 2017)
Koperasi Peternak Sapi Bandung Utara (KPSBU) is a cooperative engaged in the business of dairy farmers who process milk into yogurt. Authors conducted a study on the marketing administration in making yogurt sales report still uses Microsoft Excel as a data processing. Based on these problems the authors take the title